Diverse biological roles of PhoP/PhoQ in Pseudomonas plecoglossicida: Impact on stress responses and virulence - Meiqin Mao; Li He; Xiangyang Lin; Jianshao Wu; Pan Wang; Chuanzhong Zhu; Qingpi Yan (Aquaculture Reports)
Pseudomonas plecoglossicida is a pathogenic bacterium affecting aquatic animals, responsible for causing a highly fatal disease known as “Visceral White Spot Disease” in various economically important fish species, leading to significant economic losses. The two-component PhoP/PhoQ system plays a crucial role in bacterial responses to environmental stimuli and regulates the expression of virulence-related genes; however, its role in P. plecoglossicida has not been thoroughly studied. In this study, we constructed a phoQ gene deletion strain (ΔphoQ) and a complemented strain (C-ΔphoQ) of P. plecoglossicida to explore the biological characteristics mediated by the phoQ gene and its impact on the host. Results indicated that, compared to the wild-type strain (NZBD9), the ΔphoQ strain exhibited significant impairments in growth and swimming motility. The absence of the phoQ gene also affected the bacterium’s response to acidic conditions, low Mg²⁺ levels, and polymyxin B. Furthermore, RNA-seq analysis revealed that 486 genes were downregulated and 216 genes were upregulated in the ΔphoQ strain compared to NZBD9. Among these, genes related to flagellar assembly, two-component systems, type III secretion systems, and bacterial chemotaxis were downregulated, while genes involved in ABC transport, magnesium ion transport, type VI secretion systems, and membrane permeability were upregulated. In artificial infection experiments, the ΔphoQ strain showed significantly reduced virulence when infecting hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂), with an LD50 value of 3.931 × 104 cfu/mL. These results suggest that the PhoP/PhoQ system may play a key role in regulating the environmental adaptability and pathogenicity of P. plecoglossicida.